Should clinical laboratories adapt to the reality of chronic kidney disease in the determination of parathyroid hormone? - González-Casaus María Luisa (De Gruyter, 2021)
The contribution of the clinical laboratory to diagnostics is increasingly important since a great deal of clinical decisions rely on laboratory test results.